Penerapan matematika dasar dalam dunia teknik mesin - hidayat, nur afif (Maliki Interdisciplinary Journal, 2025)
Mathematics is at the heart of many branches of science and technology, including mechanical engineering. In engineering, mathematics provides a theoretical foundation for understanding, modeling, and solving problems that arise in mechanical systems. The important role of mathematics is seen in its ability to bridge theory and practice, which is the basis for innovation in mechanical engineering. Concepts such as algebra, calculus, and geometry have proven to be very effective tools for analyzing and designing complex mechanical systems. Mechanical engineering itself is one of the most fundamental engineering disciplines, playing a role in supporting almost all industrial sectors. The development of technology in the modern era requires engineers to be able to solve increasingly complex challenges by utilizing mathematical modeling. Through this approach, efficient, economical, and reliable mechanical systems can be designed. In this context, mathematics is not only a tool, but also a major foundation in the development of engineering solutions. In addition to providing practical solutions, mathematics also allows for in-depth analysis of the behavior of mechanical systems. Basic mathematical concepts, such as number theory, differential equations, and vector calculus, help engineers understand physical phenomena in a more structured way.